Vietnamese EFL learners’ perspectives on online extensive reading during emergency remote L2 teaching - Nhung Cam Nguyen (Studies in English Language and Education, 2022)
Previous research has shown a range of benefits of extensive reading for second or foreign language (L2) learning, as well as learners’ positive attitudes towards extensive reading. However, during emergency remote teaching around the globe as a consequence of the Covid-19 pandemic, where all L2 classes have been moved online, little research has investigated online extensive reading as well as learners’ perspectives on this activity. Therefore, the present study was conducted to investigate Vietnamese EFL learners’ perspectives on online extensive reading during emergency remote L2 teaching amidst the Covid-19 pandemic. Eighty-seven Vietnamese EFL learners at a local university participated in the study. They were involved in one online extensive reading over 12 weeks. Data were collected through semi-structured interviews with the participants. The results showed that all the learners had positive attitudes towards online extensive reading during emergency remote L2 teaching. Learners reported enjoying the variety of topics and genres found in online extensive reading, the suitability of the texts for their L2 proficiency, the usefulness of the program for enhancing their L2 competence as well as general knowledge, along with the convenience that the program offers. Learners also suggested several improvements in the website interface and the addition of more topics, genres, and quizzes.